Application of Acceptance and Commitment Therapy for Patients With Auditory Hallucinations: Case Study - Bazofi Ismail Harahap; Suhariyanto; Nurbani (Fakultas Keperawatan Universitas Andalas, 2025)
Mental disorders have become one of the global health problems today. Hallucinations are a nursing problem that is commonly found in mental disorders, especially schizophreni. Increase in the number of cases of hallucinations indicated the need for additional nursing interventions to assist nurses in providing care to patients experienxing auditory hallucinations. The purpose of this study is to investigate the effects of nursing care and the application of acceptance and commitment therapy on patients with auditory hallucinations, at the West Kalimantan Provincial Mental Hospital. This study uses a qualitative design with a case study approach. The main nursing diagnosis that was established was sensory perception disorders: auditory hallucinations. This study shows that there is a change in the frequency of hallucinations experienced to quite reduced, and the response to hallucinations experienced, such as behavior following orders from hallucinations, is reduced. There is a decrease in the PSYRATS score before the ACT, namely 26 to 15 after the ACT. Using evidence-based nursing ACT 6 sessions, nurses can provide nursing care for sensory perception disorders (auditory hallucinations) using the application of evidence-based nursing ACT 6 sessions.